Android-Based Learning Media for Three-Dimensional Geometry : A Development Study - Dewi Kartika Subekti; Ratu Ilma Indra Putri; Sugilar (Jurnal Inovasi Matematika, 2026)
This study developed an Android-based mathematics learning media for three-dimensional geometry, focusing on distance concepts using Plomp’s (Plomp & Nieveen, 2013) educational design research framework. The development involved preliminary research and prototyping, including expert review, one-to-one evaluation (5 students), small group evaluation (10 students), and a field test with 30 twelfth-grade students in a one-case study. Data were collected through expert review, practicality questionnaires, classroom observations, interview, and pretest–posttest spatial assessments. The expert review confirmed the validity of the content, linguistic, instructional design, and instructional media communication aspects, while practicality evaluation showed that the media was easy to use and engaging. Field test results indicated positive trends in students’ spatial abilities, with improvements in spatial visualization (+32.22%), spatial relations (+15.11%), and spatial orientation (+12.78%), and a significant pretest–posttest difference (t(29) = 7.22, p < 0.001), which supported the media’s potential to scaffold spatial reasoning within the design research context. Although the normalized gain was modest (0.24), this result underscores the gradual nature of spatial development and provides formative input for design refinement. Two design principles were identified: (1) integrating interactive three-dimensional visualization to bridge iconic and abstract representations, and (2) implementing active scaffolding to connect visual intuition with precise mathematical procedures.